2022
DOI: 10.1590/1413-81232022273.38782020
|View full text |Cite
|
Sign up to set email alerts
|

Diferenças na disponibilidade de medicamentos prescritos na Atenção Primária: evidências do Projeto Prover

Abstract: Resumo Estudo transversal da disponibilidade de medicamentos prescritos na Atenção Primária, com amostra probabilística de 1221 usuários das farmácias públicas de município polo de saúde em Minas Gerais, em 2017. Foram estimados indicadores de disponibilidade dos medicamentos e realizou-se regressão logística hierárquica, segundo o modelo comportamental de uso de serviços de saúde. Apenas 39,3% dos usuários receberam todos os medicamentos nas quantidades prescritas. Os medicamentos mais e menos disponíveis for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…This result confirms previous findings in the same municipality showing that the unavailability of medicines in SUS was a recurring issue in the perception of pharmacists and patients 35 . Recently, another study assessed the availability of medicines in the public system and found that only 39.4% of patients had access to all prescribed medicines 3 . The adequate provision of free medicines would reduce OOPPE Prevalence and factors associated with out-of-pocket pharmaceutical expenditure among primary healthcare patients: evidence from the Prover Project and increase access to medicines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result confirms previous findings in the same municipality showing that the unavailability of medicines in SUS was a recurring issue in the perception of pharmacists and patients 35 . Recently, another study assessed the availability of medicines in the public system and found that only 39.4% of patients had access to all prescribed medicines 3 . The adequate provision of free medicines would reduce OOPPE Prevalence and factors associated with out-of-pocket pharmaceutical expenditure among primary healthcare patients: evidence from the Prover Project and increase access to medicines.…”
Section: Discussionmentioning
confidence: 99%
“…Research carried out in the country has found widespread shortages of medicines at the public community pharmacies. Consequently, access to medicines by patients is substandard [3][4][5][6] leading them to purchase their treatments from the private sector 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Under these aspects, one of the factors that deserves to be highlighted is related to the users' accessibility to their treatment. Thus, access barriers such as PLWHIV commuting to another city to fetch their medications can lead to loss of therapeutic monitoring, as the users are usually responsible for financially paying for their transportation and, in addition, may have their income compromised, particularly for those individuals who work by production or autonomously 6 .…”
Section: Rbfhssmentioning
confidence: 99%